Kemenangan Kolom Kosong dalam Pilkada Pangkalpinang 2024: Evaluasi Kebijakan dan Hambatan Kompetisi Politik Lokal - Deni Deni; Raniasa Putra; Yan Megawandi; Darol Arkum (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2026)
This article aims to evaluate the policy implementation of the 2024 Pangkalpinang Regional Head Election (Pilkada), which was marked by the victory of the empty column, and to identify the factors hindering the emergence of alternative regional head candidates. The research problem focuses on the paradox between the procedural success of the election and the substantive failure to produce representative political competition. To address this issue, the study employs a public policy evaluation perspective by referring to the dimensions of effectiveness, efficiency, adequacy, equity, responsiveness, and policy appropriateness. This research adopts a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, literature review, and the use of relevant secondary data, and were analyzed inductively using triangulation techniques to ensure data validity. The findings indicate that although the 2024 Pangkalpinang Pilkada was conducted in accordance with legal provisions, the policy failed to produce legitimate local leadership and healthy political competition. The victory of the empty column reflects public dissatisfaction with party elite dominance, candidate nomination regulations, and the weak cadre regeneration function of political parties. This study concludes that electoral policy reform is necessary to realize more inclusive, democratic, and representative regional elections.